Intermittent pathways in the access to artistic careers in young descendants of migrants (Práxis Educativa, 2022)
By adopting an intersectionality approach, this paper aims to analyse how some social categories – ethnic-racial origin, nationality and socioeconomic context – determine the pathways of young migrants’ descendants in their access to artistic careers. Data is based on semi-structured interviews with youth from different origins (Africa, Brazil and Eastern Europe) living in Sintra, Portugal. Results indicate that differences between their access to careers related to arts, are determined by the interlink of these social categories. While in some cases, the intersection of categories reproduces their underprivileged social position and block the access to these careers; in other cases, their social position is mitigated and the access to artistic careers is facilitated. At the conclusion, we suggest the need of adopting in further investigations an intersectionality paradigm when addressing the artistic pathways of young migrants’ descendants.Keywords: Intersectionality. Professional artistic careers. Migrants’ descendants.